2015
DOI: 10.1016/j.jamda.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Epidemiology of Traditional Cardiovascular Risk Factors in the Geriatric Population

Abstract: Traditional risk factors of cardiovascular death in the general population, including body mass index (BMI), serum cholesterol, and blood pressure (BP), are also found to relate to outcomes in the geriatric population, but in an opposite direction. Some degrees of elevated BMI, serum cholesterols, and BP are reportedly associated with lower – instead of higher – risk of death among the elderly. This phenomenon is termed “reverse epidemiology” or “risk factor paradox” (such as obesity paradox) and is also obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
77
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 58 publications
9
77
1
6
Order By: Relevance
“…This hypothesis is also supported by prior observations of an association between serum B12 and two indicators of inflammation: C-reactive protein and ferritin. Also, Salles et al [18] showed a similar B12-mortality relationship in elderly adults, another population predisposed to PEW [22]. However, in our study, concurrent adjustment for B12 when folate was the exposure and vice versa did not significantly change the observed associations.…”
Section: Discussioncontrasting
confidence: 47%
“…This hypothesis is also supported by prior observations of an association between serum B12 and two indicators of inflammation: C-reactive protein and ferritin. Also, Salles et al [18] showed a similar B12-mortality relationship in elderly adults, another population predisposed to PEW [22]. However, in our study, concurrent adjustment for B12 when folate was the exposure and vice versa did not significantly change the observed associations.…”
Section: Discussioncontrasting
confidence: 47%
“…Given that the atherogenic impact of ApoB and triglyceride-rich lipoproteins typically takes effect over an extended period of time, the possibility that serum non-HDL-C levels in the short-term are more reflective of other factors, such as energy metabolism and nutrition, cannot be discounted. 41 Hence, improved outcomes can be observed in the short-term, whereas during long-term follow-up, elevated non-HDL-C levels may be associated with worse cardiovascular and all-cause mortality. 22 However, given the significant increase in the short-term risk of death in patients with ESRD and the fact that long-term survival by definition is dependent on short-term survival, the value of these observations cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…The reverse epidemiology of cardiovascular risk factors was studied in patients with CKD [16,17] and heart failure [18] and in the geriatric population [19]. Previous studies using bioimpedance analysis showed that overhydration is prevalent in leaner patients undergoing dialysis therapy [3,20].…”
Section: Discussionmentioning
confidence: 99%